OSTVARIVANJE PRAVA IZ OBAVEZNOG ZDRAVSTVENOG OSIGURANJA U KOMBINOVANOM SISTEMU FINANSIRANJA U SRBIJI - Krstić, Miroslava M (Pravni zapisi, 2018)
The right to health insurance represents one of basic human rights. The system of health care in any case can`t meet all the wants and needs of the patients because the needs and wants of the patients have a continuous growth, the health institutions become more expensive and the means of financing are becoming smaller. Patients also demand protection from financial risk from expensive health services, with respect to being sure that the health insurance funds, based on the gathered means, cover high costs of treatment, in case a need for it arises due to a serious illness. Budget financing doesn’t provide a stimulus in the doctors’ work and provides a lower quality of heath services. The principle of solidarity in the system of health services, primarily depends on the available means and the governmental decision with regards to the division of means towards the health institutions. On one hand, the system in today’s conditions functions with difficulty while on the other hand, the system of health care of a specific country follows the development, hence needs to respond to new challenges. The purpose of the work is to show a combined system of financing (capitation and diagnostic groups) ensures an increase of physical and effective availability of health care for all citizens of Serbia, leading to an advance of quality of health care as an increase of effectiveness and efficiency in providing health services. One of the objectives of the piece is to show that the combined system is financially sustainable, due to it not being dependent on budget allocation and that in such a system the citizens are protected from financial risk related to health i.e. pateient do not have to fear if, in case of serious illness and expensive medical procedures, the system can cover the high expenses of their treatment. In a combined system the providers of heath services significantly effect the division of revenue, which ensures stability in providing health care. During the making of the work, methods were used which are adapted to the problems of the research including: comparative law method, deductive method based on the method of abstraction and the statistical method. Also, an inductive method was used, which assumes an immediate insight into appropriate data and statistical analysis of documentation and comparison method, to perform the appropriate conclusions. Among used methods, special attention was given was to exemplary analysis of problems of public financing and methods of normative analysis during researching legal solutions in the area. It is often asked whether it is possible to define the most effective model of health care financing in which health insurance equity would be equally accessible to all citizens. Based on the research a conclusion was made that it is impossible to define adequate health standards and the most functional model of financing health care with the purpose of a wholesome and total achievement of rights coming from mandatory health insurance. With respect to afore mentioned: What is the best possible way of securing realization of rights from mandatory health insurance? A conclusion was reached that a combined system of financing is more suitable to Serbia and secures a better effect on social work and product because it is: more budget neutral, secures stability in providing health care, stimulates health factors and secures a higher level of satisfaction amongst clients. Keywords: rights from mandatory health insurance; system of health care; providers of health services; quality of health care; combined system of financing.